CONSTRUCTION OF RESIDENTIL BUILDINGS AND ITS IMPACT ON ENVIRONMENT - Samdani, Parth; Choudhary, M.P. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
A close coordination between environmental engineers and the construction industry has resultedin an environmental profiling system that enables designers and constructors to select materialsand components with the lowest environmental impact. Construction has long been recognised asone of the most resource-hungry and the least sustainable industries in the world. However wecontinue to depend on buildings of all kinds – our homes, offices, hospitals, shops, culturalcentres and more. Despite increasing awareness of the need to develop a sustainable approachwithin the construction industry, this proved difficult without a reliable method of evaluating andcomparing the environmental impacts of different construction materials